Las operadoras turísticas y nuevas rutas de recreación de la ciudad de Quevedo 2021 - Intriago Lass, Dayanara Mishell (2021)
In general, this project has been designed around the contribution of tour operators in the creation of new tourist recreation routes for the canton of Quevedo with a theme of historical, social, cultural, tourist and gastronomic character that allow to know and enjoy a series of common resources and attractions in an organized way. Thus, ensuring coherence through a common thread that gives meaning to the itinerary in a way that unites different places, activities and elements that act on this tourist destination and thus strengthen the tourist cadastre of the city of Quevedo in the year 2021.